2009
DOI: 10.12968/bjon.2009.18.1.32072
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracy and efficiency of early warning scores in acute care

Abstract: A hand-held computer helps to improve the accuracy and efficiency of EWS in acute hospital care and is acceptable to nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…However, inputting the same ten vignettes was on average over ten seconds quicker than paper after the nurses had used the e-Obs system for four weeks in clinical practice. [28] This improvement is similar to the smallest median ward change found in our study.…”
Section: Relevance To Other Worksupporting
confidence: 89%
“…However, inputting the same ten vignettes was on average over ten seconds quicker than paper after the nurses had used the e-Obs system for four weeks in clinical practice. [28] This improvement is similar to the smallest median ward change found in our study.…”
Section: Relevance To Other Worksupporting
confidence: 89%
“…EWSs using fewer parameters than NEWS are prone to errors in the inaccurate assignation of individual vital sign parameters to the correct EWS weighting group 27 and the calculation of the total EWS. [28][29][30] On this basis, it might be expected that NEWS would be associated with an increase in operational error over EWS with fewer parameters, but this hypothesis requires testing. Nevertheless, the electronic bedside capture of EWS data, which is increasing throughout the NHS, has been shown to reduce errors in EWS calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the electronic bedside capture of EWS data, which is increasing throughout the NHS, has been shown to reduce errors in EWS calculation. 29,30 Additionally, further work regarding the operational effectiveness of any EWS, including NEWS, compared to simpler systems of activating a rapid response team (e.g., single calling criteria 31 or subjective criteria 32 ) needs to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…71 These findings were echoed in a later study which found that a hand-held computer is acceptable to nurses and helps to improve the accuracy and efficiency of early warning scores in acute hospital care. 72 Schmidt et al associated the use of such technology with reduced patient mortality. 73 A before-and-after controlled trial of 18 305 patients investigated the effects of automated vital signs monitors 74 and found their introduction to be associated with increased survival to discharge from 86% to 92% in patients receiving rapid response team calls.…”
Section: Opportunity For Automationmentioning
confidence: 99%